Tree hollow decline in new forest reserves with a long history of logging - Gorrod, Emma; Oliver, Ian; Bedward, Michael; McAllister, Danielle; O'Kelly, Tim; Lawrie, Kristy (Austral ecology, 2024)
In many parts of the world, achieving a target of 30% of land managed for conservation under the Kunming‐Montreal Global Biodiversity Framework will require the protection of land with a long history of management for production. In newly protected forests, past logging practices will have impacted key aspects of stand structure, including hollow‐bearing trees that provide critical habitat for vertebrate fauna. The impacts of past silvicultural practices on hollow density, distribution, type and longevity may necessitate targeted ameliorative actions. We investigated tree hollows in the largest river red gum (Eucalyptus camaldulensis Denh.) forest in the world, which had undergone logging‐induced woody thickening prior to being converted to a conservation reserve in 2010. We recorded stem diameters and hollows in living and dead trees in 66 two‐hectare plots. Our sites sampled two productivity states and a wide range of total tree densities. On all sites, we found that hollow‐bearing tree densities were lower than reference values for unlogged stands and average density had halved relative to reference values. We found no relationship between the density of hollow‐bearing trees and total tree density, but we did find a weak positive relationship with site productivity. Larger trees had more hollows, bigger hollows and a greater diversity of hollow sizes. However, of the 1254 hollow‐bearing trees recorded, 43% were dead, 48% of the dead trees had been ringbarked. The proportion of hollow‐bearing trees that were dead was positively correlated with tree size, with 60% of trees in the largest quartile (>105 cm) recorded as dead. The prevalence of dead hollow‐bearing trees suggests that the density and diversity of hollows will continue to decline and ameliorative actions should be considered. These results highlight the need to consider the legacy of past silvicultural practices in the management of newly created conservation reserves.